Normativity of cooperation in theater classes (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article proposes the distinction and pedagogical treatment of elements of normativity acting in the practice of theatrical exercises and games in the planning and conduction of theater classes in schools, particularly in situations where joint attention and cooperation operate. The initial intentions of this approach are to increase the investigative quality of these classes, with the consequent improvement in the specification of the contents worked on, and the constitution of resistance actions and concrete answers to some argumentative elements present in politically reactionary proposals in Brazil, more active since the year of 2016 and consolidated in the 2018 elections.
Keywords: Theater education; Politics; Normativity; Cooperation; Joint attention